Brebel LA 49: En bosættelse under overgangen fra ældre til yngre romersk jernalder i nærheden af Thorsberg Mose - Schulze, Rolf (Arkæologi i Slesvig-Archäologie in Schleswig, 2026)
The excavation of the site Brebel" LA 49 near the well-known Thorsberg bog deposit allows the closing of a research gap. Until recently, we only knew where the Angles in the Roman Iron Age buried their dead and where they sacrificed to their gods, but we did not know where they lived. !e excavation carried out between 2021 and 2024 yielded a settlement with at least fifteen longhouses and secondary structures like fences, roofed fences and storehouses, alongside some Bronze Age pits and, notably, an inhumation grave from the early stages of the Funnel Beaker Culture. Several well-preserved houses, one of which had remains from a burned and collapsed timber wall still in situ, give a detailed account of Early to Late Roman Iron Age construction work and everyday life. Although only one of the farmsteads was preserved with all its fences and secondary buildings, it is highly probable that also the other longhouses were parts of larger farmsteads, as indicated by the presence of numerous structures in their surroundings. One hall-house found in the very centre of the settlement probably had a special, centralized function, thus giving a hint that the settlement was more than a mere accumulation of farmsteads: It was a village. It is highly probable that the villagers were aware of the depositions at Thorsberg or even participated in the offerings there.The abandonment of the settlement at the end of the Roman Iron Age agrees well with the historical reports about the largescale migration of Angles to Britain.